2005
DOI: 10.1111/j.1468-0351.2005.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐entering Europe: Does European Union candidacy boost foreign direct investment?

Abstract: This study examines the ability of the Central and Eastern European countries to attract foreign direct investment during the first decade of transition. After considering a model of profit maximizing firms, we undertake an empirical investigation of the factors that determine multinational firms' location decisions within Europe. We find empirical support for the traditional market size and cost factors. In addition, we examine the effect of key European Union announcements regarding the accession process. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 28 publications
3
35
0
6
Order By: Relevance
“…Despite quite weak correlations in the p-value of the models, which show less than 0.05 in all the cases, they seem significant. Thus, our findings do not contradict other results that emphasise the role of market size in fDi attraction (Bevan & eStrin 2004;caSi & reSMini 2010;ClausiNg & DoroBaNțu 2005;DaNCiu et al 2011;deMeKaS et al 2007). in addition, a lag-time certainly must occur between fDi-induced growth and gDP growth (PeliNesCu & răDulesCu 2009).…”
Section: Resultssupporting
confidence: 66%
“…Despite quite weak correlations in the p-value of the models, which show less than 0.05 in all the cases, they seem significant. Thus, our findings do not contradict other results that emphasise the role of market size in fDi attraction (Bevan & eStrin 2004;caSi & reSMini 2010;ClausiNg & DoroBaNțu 2005;DaNCiu et al 2011;deMeKaS et al 2007). in addition, a lag-time certainly must occur between fDi-induced growth and gDP growth (PeliNesCu & răDulesCu 2009).…”
Section: Resultssupporting
confidence: 66%
“…This is well documented that capital market integration follows the economic integration. Clausing and Dorobantu (2005) reported that investors would divert funds to those markets (economies) which are open to trade and enjoy the stable economic environment. Davis (2012) also considered bilateral trade integration as an important and supportive factor for fruitful integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, we included a variable that captures whether a country is a European Union (EU) member, because this has been shown to matter for attracting FDI (Bevan & Estrin 2004;Clausing & Dorobantu 2005;Cirtautas & Schimmelfennig 2010). This is a country and time-varying dummy variable that equals 1 when a country is an official member of the EU.…”
Section: Data and Methods For Regression Analysismentioning
confidence: 99%